Meningkatkan Potensi Usaha Mikro Berbasis Ekonomi Kreatif bagi Anggota Koperasi melalui Program Pemberdayaan dan Peran Koperasi Syariah (Studi Penelitian di Koperasi Syariah Tangerang Selatan) - Nurranto, Heri; Gayatri, Askardiya Mirza; Muzdalifah, Muzdalifah (Sosio e-Kons, 2019)
This research aims to increase the potential of a micro-economy based creative economy through empowerment programs and the role of CMS Syariah Cooperatives with 92 members. This study uses a qualitative method. The data needed is primary and secondary data obtained from the chairman of the cooperative, the ranks of the cooperative management and members of the cooperative who have micro-businesses. The population of cooperative members who have micro-businesses is 9, all of which are sampled. Data collection through field observations, discussions, interviews, and documentation. The results showed that members of cooperatives that have micro-businesses really need creative economic knowledge, motivation, and coaching, including assistance in developing products and services so that they can contribute to CMS Cooperatives as a place for their businesses that will automatically turn on CMS Cooperative operations.